1999
DOI: 10.1073/pnas.96.11.6199
|View full text |Cite
|
Sign up to set email alerts
|

PTEN modulates cell cycle progression and cell survival by regulating phosphatidylinositol 3,4,5,-trisphosphate and Akt/protein kinase B signaling pathway

Abstract: To investigate the molecular basis of PTENmediated tumor suppression, we introduced a null mutation into the mouse Pten gene by homologous recombination in embryonic stem (ES) cells. Pten ؊/؊ ES cells exhibited an increased growth rate and proliferated even in the absence of serum. ES cells lacking PTEN function also displayed advanced entry into S phase. This accelerated G 1 ͞S transition was accompanied by down-regulation of p27 KIP1 , a major inhibitor for G 1 cyclindependent kinases. Inactivation of PTEN i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
583
3
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 716 publications
(612 citation statements)
references
References 31 publications
(37 reference statements)
22
583
3
4
Order By: Relevance
“…Considerable controversy exists as to the e ects of PTEN on cell proliferation, viability and anoikis (Cheney et al, 1998(Cheney et al, , 1999Davies et al, 1998Davies et al, , 1999Furnari et al, 1997Furnari et al, , 1998Li and Sun, 1998;Stambolic et al, 1998;Podsypanina et al, 1999;Ramaswamy et al, 1999;Sun et al, 1999;Tian et al, 1999). In the current study, induced expression of PTEN in PTEN de®cient breast cancer cells, was associated with a marked decrease in the basal phosphorylation of AKT, p70S6 kinase, BAD, and GSK3a, alterations indicative of decreased activity and signaling through the PI3K pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considerable controversy exists as to the e ects of PTEN on cell proliferation, viability and anoikis (Cheney et al, 1998(Cheney et al, , 1999Davies et al, 1998Davies et al, , 1999Furnari et al, 1997Furnari et al, , 1998Li and Sun, 1998;Stambolic et al, 1998;Podsypanina et al, 1999;Ramaswamy et al, 1999;Sun et al, 1999;Tian et al, 1999). In the current study, induced expression of PTEN in PTEN de®cient breast cancer cells, was associated with a marked decrease in the basal phosphorylation of AKT, p70S6 kinase, BAD, and GSK3a, alterations indicative of decreased activity and signaling through the PI3K pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Enforced expression of PTEN has been reported to result in decreased cell proliferation and decreased tumorigenicity (Cheney et al, 1998(Cheney et al, , 1999Furnari et al, 1998;Li and Sun, 1998;Tamura et al, 1999;Tian et al, 1999), an observation attributed to the ability of PTEN to induce cell cycle arrest, apoptosis or anoikis, a form of apoptosis that occurs when cells are dissociated from their extracellular matrix (Davies et al, 1998(Davies et al, , 1999Frisch and Ruoslahti, 1997;Furnari et al, 1998;Li and Sun, 1998;Sun et al, 1999;Ramaswamy et al, 1999;Stambolic et al, 1998). However, a consensus has not been reached on whether the capacity of PTEN to modulate these processes is determined by cell lineage or culture conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 4E, the luciferase activities of different 5 0 -truncated PTEN promoter constructs that contain the Egr1-binding site were reduced by E-cadherin loss, whereas the luciferase activity of a full-length construct with a mutated Egr1-binding site, pGL3-PTEN2526/427(mutEgr1), was low in both control and shEcad-transfected SKOV-3 cells. As E-cadherin regulates PTEN, which has previously been implicated in the suppression of cell growth (Ramaswamy et al, 1999;Sun et al, 1999), we investigated whether the overexpression of PTEN regulates cyclin D1 and p27 Kip1 protein levels. Transient transfection of SKOV-3 cells with PTEN decreased cyclin D1 and increased p27 Kip1 protein levels ( Figure 4F).…”
Section: Loss Of E-cadherin Inhibits Pten Transcription Via Egr1 Downmentioning
confidence: 99%
“…Specifically, in breast cancer, cell line analyses have shown that PTEN appears to suppress breast cancer growth by down-regulation of PI3K, with resultant G1 arrest and cell death (6,7). Studies of embryonic stem cells have shown that cells featuring mutations of the PTEN gene exhibited an increased growth rate and displayed an advanced entry into S-phase (8). The accelerated G 1 /S transition was accompanied by down-regulation of p27, a major inhibitor of G 1 cyclin-dependent kinases.…”
mentioning
confidence: 99%